1988
DOI: 10.1111/j.1532-5415.1988.tb04395.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Associated Hospital Admissions in Older Medical Patients

Abstract: A survey of drug-related admissions of patients aged 50 years and older was conducted at the Health Sciences Centre, Winnipeg to determine the interrelationship of risk factors, and isolate the effect of age. All nonelective medical admissions were prospectively assessed to determine the role of drug therapy as a contributory factor. Of the 863 eligible admissions, 162 exhibited at least one drug-related adverse patient event (DRAPE) at the time of hospitalization. This accounted for 19% of the admissions (23%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
0
4

Year Published

1990
1990
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(136 citation statements)
references
References 19 publications
(38 reference statements)
5
127
0
4
Order By: Relevance
“…There are numerous contributing causes of the overall adverse event rates, including errors in dispensing, monitoring and adherence to medications (Avery et al 2002). They may drive up to a quarter of all hospital admissions (Grymonpre et al 1988;Hurwitz 1969;Ives et al 1987;May et al 1977), and this problem will likely be magnified by the increasing prevalence of chronic comorbidities in an increasingly aged population who also live in a culture of widespread over-the-counter medication use and acceptance of polypharmacy.…”
Section: The Challengementioning
confidence: 99%
“…There are numerous contributing causes of the overall adverse event rates, including errors in dispensing, monitoring and adherence to medications (Avery et al 2002). They may drive up to a quarter of all hospital admissions (Grymonpre et al 1988;Hurwitz 1969;Ives et al 1987;May et al 1977), and this problem will likely be magnified by the increasing prevalence of chronic comorbidities in an increasingly aged population who also live in a culture of widespread over-the-counter medication use and acceptance of polypharmacy.…”
Section: The Challengementioning
confidence: 99%
“…They may present with harmful outcomes, resulting in about 2.8% of all hospitalizations in older patients and an estimated cost of more than U$1 billion per year, to government exchequer health care systems [1][2][3]. Previous studies [4,5] which were mainly centered around patients of emergency departments and hospital wards showed that the cardiovascular drugs were the most common culprits to cause DDIs.…”
Section: Introductionmentioning
confidence: 99%
“…Any medication switch at the same time also constitutes an opportunity to review medications used by a patients which may result in a reduction in the number of drugs used simultaneously that is known to be the strongest risk factor for adverse events [14,15].…”
Section: Clinical Rationale For Rdps: Therapeutic Substitutionmentioning
confidence: 99%